A rare concomitance of Wilson’s disease and systemic lupus erythematosus in a teenage girl: a case report and literature review - Yang, Zigui; Su, Yashuang; Liu, Meilu; Sun, Lijun; Zhang, Fengxiao; Lin, Wei (Frontiers in Pediatrics, 2024)
Background: Wilson's disease (WD) is an inherited disorder characterized by impaired biliary excretion of copper and excessive copper accumulation in multiple organs, primarily leading to hepatic, neurological, and psychiatric manifestations. The coexistence of WD and systemic lupus erythematosus (SLE) has rarely been reported, posing challenges in accurately diagnosing these two conditions owing to overlapping clinical symptoms.Case presentation:We presented the case of a 17-year-old girl initially suspected of having SLE due to positive anti-nuclear antibodies (ANA) and lupus anticoagulant (LA), decreased platelet count, hypocomplementemia, and pleural effusion. However, the patient also exhibited an unusual manifestation of decompensated liver cirrhosis, which is not typical of SLE. Further investigation revealed low serum ceruloplasmin levels, high 24-hour urine copper levels, the presence of Kayser-Fleischer (K-F) rings, and a compound heterozygous mutation in the ATP7B gene confirming the diagnosis of WD.Conclusion:The co-occurrence of WD and SLE poses a significant diagnostic challenge, often leading to misdiagnosis and delayed diagnosis. Therefore, in patients with well-controlled SLE presenting with unexplained liver fibrosis, neurological involvement, or psychiatric symptoms, it is crucial to consider the possibility of WD.However, further studies are required to elucidate the underlying pathophysiological mechanisms.